2018
DOI: 10.1016/j.mcn.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomes contribute to oxidative stress in neurons during doxorubicin-based chemotherapy

Abstract: Doxorubicin, a commonly used anti-neoplastic agent, causes severe neurotoxicity. Doxorubicin promotes thinning of the brain cortex and accelerates brain aging, leading to cognitive impairment. Oxidative stress induced by doxorubicin contributes to cellular damage. In addition to mitochondria, peroxisomes also generate reactive oxygen species (ROS) and promote cell senescence. Here, we investigated if doxorubicin affects peroxisomal homeostasis in neurons. We demonstrate that the number of peroxisomes is increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 88 publications
1
24
0
Order By: Relevance
“…The behavior of larvae treated with 50 µg/ml of DOX could be a result of both effects observed for lower and higher concentrations and was observed as a movement similar to the untreated control. These results are in accordance with previous works which showed that DOX induced cytotoxic effects in vitro in primary cultured neurons, and in vivo produced neurotoxic effects in the brain of mice and rat (Kosoko et al, 2017;Moruno-Manchon et al, 2018). Even though DOX poorly crosses the bloodbrain barrier (BBB) in humans, it still arrives at the brain at doses sufficient to cause neurotoxicity (Kesler and Blayney, 2016).…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…The behavior of larvae treated with 50 µg/ml of DOX could be a result of both effects observed for lower and higher concentrations and was observed as a movement similar to the untreated control. These results are in accordance with previous works which showed that DOX induced cytotoxic effects in vitro in primary cultured neurons, and in vivo produced neurotoxic effects in the brain of mice and rat (Kosoko et al, 2017;Moruno-Manchon et al, 2018). Even though DOX poorly crosses the bloodbrain barrier (BBB) in humans, it still arrives at the brain at doses sufficient to cause neurotoxicity (Kesler and Blayney, 2016).…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…Cortices from rat embryos (E17 and E18) were dissected, dissociated, and plated on 24-well tissue-culture plates (4 × 10 5 per well) coated with poly- d -lysine (BD Biosciences, San Jose, CA) as described 17 , 23 , 73 , 74 . Primary cortical neurons were grown in Neurobasal Medium (Life Technologies, Carlsbad, CA) supplemented with B-27 (Life Technologies), GlutaMAX (Life Technologies), and penicillin–streptomycin (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, eNOS expression, which is associated with the function of HUVECs (51), was reinstated by treatment with Ator. Alteration in the cellular microenvironment ultimately leads to cell aging (54). In the current study, Ator delayed Ang II-induced aging by maintaining cellular homeostasis.…”
Section: Discussionmentioning
confidence: 51%